Vocational Education Expansion Policy: Implications on Student Participation and Graduate Quality - Wuandari, Anisya; Lestari, Annisa Ayu; Fata, Safira Fitrotul (Proceedings Series on Social Sciences & Humanities, 2025)
Vocational education plays an important role in preparing learners to have high competence and readiness to enter the world of work. Since the enactment of Presidential Instruction Number 9 of 2016 regarding the revitalization of SMK, the government has made various improvement efforts, such as curriculum adjustments and increased collaboration with the business world and industry. However, data shows that SMK graduates still dominate the open unemployment rate in Indonesia, indicating that there are challenges in the implementation of the policy. This article aims to analyze the policy of increasing student participation in vocational education and its relationship with the quality of learning and graduate work readiness. The study is carried out with a conceptual approach and literature analysis. The results of the discussion show that the SMK Pusat Keunggulan program contributes positively to improving the quality of education, although there are still obstacles such as limited facilities, low quality of teaching, and a curriculum that is not fully adaptive to the needs of the industry. This finding confirms the need for a relevant, inclusive, and sustainable vocational education development strategy so that vocational school graduates are more ready to compete in the job market.